Prinsip Hukum Dalam Penyusunan dan Pelaksanaan Kontrak Engineering Procurement Construction (Kontrak "EPC") - Dwi Mariyati (Yuridika, 2018)
The EPC Contract is the form of contract that is currently used by the contractors to take over construction work. The EPC Contract having three activities, the engineering design , procurement and construction execution, that are integrated. For the activity EPC Contract is the Single Contractor must be responsible for the design of jobs and accuracy, and requirement of the owner project, until construction. This contract type commonly have a high risk, the finals price, and the accuracy of the period for implementation. Characteristic of EPC Contract is industry building activities that are proces plant and industry plant. The purpose of which are going to achieved in EPC Contract to preset specifications to fulfill the requirements specified in terms of the time, the quality and expenses.The main issues in this legal research are the legal principle that is used in the preparation of EPC Contract and the principle of law in the implementation of  EPC  Contract  in Indonesia. The type of research is the normative study and the approach of this research having four methods approach among others are statute approach, conceptual approach, cases approach,  and comparative approach.The result of this research there are four the most important among others are the first is legislation, the second is the implementation of regulation, the third is EPC institution procurement and  fourth is the form of EPC Contract.